Psychological Analysis - Sarhan, Adam (Ascent Audio, 2022)
Conventional wisdom tells us that people are rational and make rational decisions with their money. But that's simply not true considering most people fail to beat the market. Conventional wisdom also tells us that there are two primary ways to approach the market: technical and fundamental analysis. Again, that is not true because if it were, everyone would be rich. It's obvious that something is missing. Author Adam Sarhan, founder and CEO of 50 Park Investments, developed a new approach, titled Psychological Analysis (PA). Coined by the author, PA teaches you how to make rational, not emotional, decisions with your money and shows you how to analyze both the individual and collective market mindset at a particular time based on the behavior and decision-making of people in the real-world. Psychological Analysis is designed to tip the odds of success in your favor. This invaluable guide helps you: make rational, not emotional, decisions with your money-especially when you are under pressure; understand the psyche of the market so you can learn how to join the Smart Money Circle and consistently take money out; generate above average returns in all market environments; and incorporate Psychological Analysis into your overall trading and investing strategy so you can make smarter decisions on and off Wall Street.